Perceptions of practitioners on the importance and achievement of research and social implementation activities on marine and freshwater carbon - Watanabe, Satoshi; Maruya, Yasuyuki; Yano, Shinichiro; Nakayama, Keisuke (Frontiers in Marine Science, 2023)
Research and social implementation related to carbon in marine and freshwater ecosystems are increasingly gaining emphasis in the global quest to achieve carbon neutrality. It is important not only to advance academic research, but also to solve practical problems for improved understanding, maintenance, and dissemination of information on carbon in marine or freshwater areas. In this study, we conducted a questionnaire survey of participants in activities related to carbon in marine or freshwater areas in Japan to clarify which issues were considered important and their understanding of the degree to which activities related to carbon in marine or freshwater areas had been achieved. Based on the responses to all questions, 77.9% of respondents, on average, among the practitioners in marine areas recognized the importance of the program strongly, while 46.5% recognized that the degree of achievement was insufficient. This tendency was more pronounced for carbon in freshwater than in marine areas(72.2% and 48.6%, respectively). The results, grouped by respondent attributes, revealed that the perception of importance and level of achievement varied depending on the organization of the activity, age, and years of knowledge of carbon in marine and/or freshwater areas. Practitioners with greater experience and those working on specific implementations perceived implementation-related aspects as more important and less accomplished than academic ones. This study provides valuable insights into the research aspects of carbon in marine and/or freshwater areas to achieve carbon neutrality.